A dinâmica da justiça: um estudo a partir de Hannah Arendt - Suárez, Nuria López Cabaleiro (2018)
Starting from the factual premise studied by Arendt on the diversity and fluidity of moral judgments, particularly in the context of totalitarian regimes, this thesis analyses her last writtens in order to find in them relevant elements (variables) that could be articulated composing our judgments. Starting from a rupture with the isolation of the heideggerian subject, accept Jasper´s Existenz and open to the other, on the terms of the reading she does of Kant, both in a intrasubject perspective, from the enlarged mentality, and in a extrasubject perspective, pointing to a political philosophy rooted in a theory of action, whose lines could return to her early writtens. Furthermore, it highlights possible uses of Arendt´s studies as a philosophical model to recent researches about cognition and justice in neurosciences and also in the dialog with recent theories of justice, preponderantly turned to political philosophy. So it demonstrates, in a study from Hannah Arendt, the relevance of her work, that is able to provide a interdisciplinary vison of the dynamics of what we understand as justice